(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This paper involves the increase in students’learning motivation because of using technology-based media in a botany class. The differences between the academic results of the students who used computer technology in botany and the students who studied according to the traditional teaching method are analyzed.